2006
DOI: 10.1111/j.1750-3841.2006.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐Drying of Amylase Hydrolyzed Sweetpotato Puree and Physicochemical Properties of Powder

Abstract: Spray‐drying, which has been used for commercial production of functional ingredients from several fruits and vegetables, has not yet been studied for sweetpotato processing. Thus, the objective was to determine the effects of viscosity reduction of sweetpotato puree with alpha‐amylase, maltodextrin (MD) addition, and inlet air temperature on the physicochemical characteristics of spray‐dried sweetpotato powder. A face‐centered cube design was used to evaluate the effects of amylase level (0, 3.75, and 7.5 mL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
116
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(158 citation statements)
references
References 22 publications
32
116
1
2
Order By: Relevance
“…in the following pairs of experiments: 3,5 and 4,6) reveals that a lower bulk density was observed in those samples which were dried using GA in comparison to those dried with MD. As shown in the Table 1, GA/honey mixtures had higher viscosity than MD/honey, which could lead to the production of larger droplets and particles, and this parameter is known to be negatively correlated with the bulk density: as typically, bulk density increases upon particle size decrease [Goula & Adamopoulos, 2005;Grabowski et al, 2006].…”
Section: Powders Loose and Tapped Bulk Densitymentioning
confidence: 99%
“…in the following pairs of experiments: 3,5 and 4,6) reveals that a lower bulk density was observed in those samples which were dried using GA in comparison to those dried with MD. As shown in the Table 1, GA/honey mixtures had higher viscosity than MD/honey, which could lead to the production of larger droplets and particles, and this parameter is known to be negatively correlated with the bulk density: as typically, bulk density increases upon particle size decrease [Goula & Adamopoulos, 2005;Grabowski et al, 2006].…”
Section: Powders Loose and Tapped Bulk Densitymentioning
confidence: 99%
“…Numerous materials, such as wall materials (encapsulating agents), are available for spray drying microencapsulation of food flavors (JAFARI et al, 2008;YANG;XIAO;DING, 2009). Gum Arabic is used by the flavor industry in spray drying applications protecting the core material from oxidation and volatilization (SHAIKH; BHOSALE; SINGHAL, 2006).…”
Section: Experimental Designmentioning
confidence: 99%
“…Ahmed et al (2010), in a study on encapsulation of purple sweet potato by spray drying, found solubility values ranging from 40.24 to 56.95%. Several reports attribute superior properties to other carrier agents related to water solubility, such as maltodextrin (GRABOWSKI; TRUONG; DAUBERT, 2006;AMOPOULOUS, 2010).…”
Section: Porositymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tonon et al (2008) at higher inlet air temperatures, there is a greater temperature gradient between the atomized feed and the drying air, resulting in a greater driving force for water evaporation, thus producing powders with lower moisture content. Grabowski et al (2006) also observed a reduction of powder moisture content with increasing temperatures, studying the spray drying of sweet potato puree.…”
Section: Resultsmentioning
confidence: 88%